Computational and experimental approaches for chitosan-based nano PECs design: Insights on a deeper comprehension of nanostructure formation. (15th February 2021) - Boni, Fernanda Isadora; Cury, Beatriz Stringhetti Ferreira; Ferreira, Natália Noronha; Teixeira, Deiver Alessandro; Gremião, Maria Palmira Daflon
Graphical abstract: Highlights: Chitosan-based nano PECs were rationally designed for methotrexate delivery. pH effect on ionization degree of materials was estimated by computational study. Spatial arrangements of polymers were predicted by quantum chemical calculation. Interaction energies of materials were addressed by PM7 semi-empirical method. Positively charged nano PECs were successfully obtained for methotrexate delivery. Abstract: Nanostructured polyelectrolyte complexes (nano PECs) based on biopolymers are an important technological strategy to target drugs to the action and/or absorption site in a more effective way. In this work, computational studies were performed to predict the ionization, spatial arrangement and interaction energies of chitosan (CS), hyaluronic acid (HA), and hypromellose phthalate (HP), for the design of nano PEC carriers for methotrexate (MTX). The optimal pH range (5.0–5.5) for preparing nano PECs was selected by experimental and computational methodologies, favoring the polymers interactions. CS, HA, HP and MTX addition order was also rationalized, maximizing their interactions and MTX entrapment. Spherical nano-sized particles (256–575 nm, by dynamic light scattering measurement) with positive surface charge (+25.5 to +29.2 mV) were successfully prepared. The MTX association efficiency ranged from 20 to 32 %. XRD analyses evidenced the formation of a new material with an organized structure, in relation to raw polymers.